2016
DOI: 10.18632/oncotarget.11228
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors of brain central neurocytoma

Abstract: Background & AimsThis study is designed for the clinical characteristics and prognostic factors of central neurocytoma (CN).MethodsCN patients from 2004 to 2012 were enrolled from the Surveillance Epidemiology and End Results (SEER) data. Clinical characteristics including age, sex, race, tumor size, tumor number, surgery, and radiation therapy were summarized. Univariate and multivariate analysis were performed to explore the prognostic factors of CN.ResultsCN tended to be borderline malignant and single lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…Central neurocytoma is a tumor of the young adults as observed in the results of the current study (mean age 24.75 years) and supported by the literature [4,5,8,9,11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Central neurocytoma is a tumor of the young adults as observed in the results of the current study (mean age 24.75 years) and supported by the literature [4,5,8,9,11].…”
Section: Discussionsupporting
confidence: 90%
“…The affection of such a young age group makes safe radical resection of that relatively benign tumor a common demand and a surgical gold standard that can help avoid radiation therapy [5,8,9,17,18]. However, postoperative radiation therapy and/or chemotherapy may be recommended for atypical neurocytomas and for recurrent cases and was not needed in our cohort [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reports demonstrated no gender predilection [ 13 , 14 ]. However, some studies showed slight male predominance [ 9 , 10 ] with one retrospective study showed female predominance [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…CN is typically deeply seated in midline structures, most commonly in the frontal horn of the lateral ventricle adjacent to foramen of Monro and attached to septum pellucidum which might extend to the third ventricle [ 11 , 13 , 15 ]. Nevertheless, there were some cases which reported other locations of neurocytoma, such as isolated neurocytoma in the fourth and third ventricles [ 14 , 16 ], and extraventricular neurocytoma in spinal cord and brain parenchyma [ 11 , 13 , 14 ]. CN tends to be benign tumor though malignant variants were reported [ 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%